Exploring Students’ Oral Communication Problems and Strategies in the Intermediate Communication Skill Course - Novita Wulandari (Universitas Negeri Surabaya, 2025)
This study aims to find out the most common communication problems and strategies used in the Intermediate Communication Skill course. This research was carried out at the State University of Surabaya by involving 100 students from the 2024 cohort who are currently in their second semester. This study employed descriptive quantitative study by using 95% confidence level and 7% margin of error, involving a sample of 100 students out of a total population of 234. The data were collected through closed and open-ended questionnaires adopted based on Dornyei and Scott (1997) taxonomy of communication problems and strategies. The data were analyzed by using SPSS with descriptive statistics, including mean and standard deviation, then supported by the responses from the open-ended questionnaire. The result of the study shows that students often face problems related to processing time performance problem and tend to use strategies such as asking for repetition, use of fillers, and asking for clarification during the Intermediate Communication Skill course. These findings suggest that students tend to select specific strategies depending on the communication problems they encounter. Therefore, it is recommended that students are encouraged to apply appropriate strategies according to the problems they face. It is also suggested that lecturers incorporate more varied learning activities to help students use communication strategies more effectively.